PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI PENGGUNAAN MEDIA GAMBAR BERBASIS PERMAINAN - Ariyati, Tatik (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2016)
The objective of this research was to increased read beginning through visual media. It was an action research conducted in Banyumas, Central Java in 2013. The stage of this action research were consist of plan, act, observe, and reflect. The subject of this research was the kindergarten students of TK Aisyiah, Rawalo, Banyumas that had read beginning problems. The method used in collecting data was a non test method which consist of survey records based on observation and observation photos. Data percentage analysis method used in this research is using archieved 80 percent. The result of overall data percentage analysis was a 97,61 percent which above the achievement indicator. Based on the increased percentage so the hypothesis can be accepted. Futhermore it can be concluded that visual media can increase read beginning for kindergarten students. The implication of this research is that visual media can be an alternative way to read beginning for kindergarten students. The implementation of visual media in read beginning at school was involved by few factors such as teacher’s ability, school facilities, and students. By the synergy of those factors students counting ability would optimally increase.